Gold‐Catalyzed Cyclization Processes: Pivotal Avenues for Organic Synthesis. Issue 1 (11th November 2015) - Kumar, Amit; Singh, Sukhdev; Sharma, Sunil K.; Parmar, Virinder S.; Van der Eycken, Erik V.
Abstract: Over the years, gold catalysis has materialized as an incredible synthetic approach among the scientific community. Due to the trivial reaction conditions and great functional compatibility, these progressions are synthetically expedient, because practitioners can implement them to build intricate architectures from readily amassed building blocks with high bond forming indices. The incendiary growth of gold catalysts in organic synthesis has been demonstrated as one of the most prevailing soft Lewis acids for electrophilic activation of carbon‐carbon multiple bonds towards a great assortment of nucleophiles. Nowadays, organic chemists consistently employ gold catalysts to carry out a diverse array of organic transformations to build unprecedented molecular architectures. Despite all these achievements and a plethora of reports, many vital challenges remain. In this account, we describe the reactivity of various gold catalysts towards cyclization processes developed over the years. These protocols give access to a wide scope of polyheterocyclic structures, containing different medium‐sized ring skeletons. This is interesting, as the quest for highly selective reactions to assemble diversely functionalized products has attracted much attention. We envisage that these newly developed chemo‐, regio‐, and diastereoselective protocols could provide an expedient route to architecturally cumbersome heterocycles of importance for the pharmaceutical industry. Abstract : Golden catalysis : Gold‐catalyzed approaches have emerged as incredible synthetic opportunities among the scientific community. Due to the trivial reaction conditions and great functional group compatibility, these protocols are synthetically convenient to assemble complex architectures, starting from readily accessible building blocks with high bond forming indices. In this account, we describe the reactivity of various gold catalysts towards intramolecular cyclization processes developed over the years. These protocols give access to a wide scope of polyheterocyclic structures, containing different medium‐sized ring skeletons. We envisage that these gold‐catalyzed (chemo‐/regio‐/diastereo‐selective) protocols could provide an efficient platform to synthesize biologically important heterocyclic cores and will find their applications in natural product synthesis.